Pendidikan feminis dalam novel Putri Kalingga karya Wibawa Wibidharma - Wiyatmi, Wiyatmi; Sudiati, Sudiati; Artanti, Yeni (Universitas Mulawarman, 2024)
Putri Kalingga [Princess Kalingga] is one of the literary works that deals with feminist education issues, especially in the Ancient Mataram Era (7th century). The novel revolves around Shima, the daughter of the Kalingga Kingdom who received religious education at Sutha Vihara and martial arts at Kalingga Kingdom. This research aims to understand the educational process that Shima in studying Buddhism, and various kinds of knowledge and skills in playing with weapons. Qualitative feminist methods are used to analysed data from the novel Putri Kalingga by Wibawa Wibidharma (2022). The results showed that feminist education had been implemented in the Kingdom of Kalingga (7th century). There were two models of feminist education in the Kalingga Kingdom era, namely private education and education in dormitories (vihara). Private education was given by parents (rishi and mpu) to their daughters, which included various kinds of knowledge, using weapons and self-defense. In the dormitory, women were trained to become nuns, studying religion (Buddhism), law, leadership and trade, as well as self-defense. This education prepares women to play important roles in society.